Analisis Faktor yang Mempengaruhi Nilai Perusahaan Menggunakan Data Panel - Imam Hidayat; Petty Aprilia Sari (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2021)
The reason for this research is to dissect the variables that influence companies that are eligible to use board information. To have the option to give success to investors, organizations should have the option to draw in financial backers by keeping up with and producing great corporate worth. Many variables influence the worth of the organization, both inner and outside. These elements incorporate Institutional Proprietorship, Capital Construction, Organization Size. This examination was led with the assistance of EViewss rendition 9. The populace utilized was 65 organizations in the property and land area. This concentrate likewise utilized purposive inspecting strategy and acquired 34 examples that coordinated with the perception information rules, specifically 170 information. The outcomes show that institutional proprietorship has no impact on firm worth, while capital design and firm size to some degree influence firm worth.